Hsa-miR-27a-3p overexpression in men with nonobstructive azoospermia: A case-control study - Hamid Norioun; Majid Motovali-bashi; Seyed Morteza Javadirad (Shahid Sadoughi University of Medical Sciences, 2020)
Background: The role of KDM3A and its downstream genes in male fertility has been approved in animal models. Additionally, the expression shrinkage of KDM3A is significantly correlated with human azoospermia phenotype. Aberrant expression of micro-RNAs could mislead spermatogenesis and mostly lead to diverse phenotypes of male infertility. Objective: The aim of this study was to evaluate the expression level of hsa-miR-27a-3p in azoospermic men to reveal its possible association with infertility. Materials and Methods: This case-control study was conducted on 30 azoospermic men, of whom, 19 had non obstructive azoospermia (NOA) and 11 obstructive azoospermia (OA) according to the pathological examinations. Comprehensive bioinformatics investigations were performed securely and hsa-miR-27a-3p was selected afterward. Reverse Transcriptase-quantitative polymerase chain reaction (RT-qPCR) method was used and statistical analysis was performed to compare the expression level of hsa-miR-27a-3p in both OA and NOA individuals. Results: In silico analysis suggested hsa-miR-27a-3p, with its potential binding ability to target KDM3A transcripts. The expression analysis of candidate hsa-miR-27a-3p indicated its significant overexpression in NOA men. Conclusion: The hsa-miR-27a-3p was overexpressed in NOA men compared to OA-control individuals. As a consequence, the overexpressed micro-RNA could downregulate directly KDM3A and indirectly TNP1 and PRM1. Therefore, spermatogenesis could be misled and male infertility could be developed.